2020
DOI: 10.3168/jds.2019-17830
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bismuth subnitrate on in vitro growth of major mastitis pathogens

Abstract: The mode of action of bismuth subnitrate in teat sealant formulations as a preventative for intramammary infections during the dry period is unknown. Although previous studies proposed an action mechanism-creating a physical barrier in the teat canal to prevent bacterial invasion-it has not been proven experimentally. We hypothesized that bismuth subnitrate has an inhibitory effect on bacterial growth, in addition to its barrier effect. The objective of this study was to assess the effect of bismuth subnitrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…We hypothesize this might be due either to the fact that no samples could be taken in the dry period, or because the internal teat sealant might have a negative influence on the survival of S. chromogenes IM in the dry period. Indeed, a negative effect of bismuth subnitrate on the in vitro growth of major mastitis pathogens was already described by others [54]. Therefore, our study data suggest that a quarter is more likely to be colonized with S. chromogenes IM during the entire dry period if a dose of 10 000 000 CFU is used in a quarter that is not sealed.…”
Section: Discussionsupporting
confidence: 72%
“…We hypothesize this might be due either to the fact that no samples could be taken in the dry period, or because the internal teat sealant might have a negative influence on the survival of S. chromogenes IM in the dry period. Indeed, a negative effect of bismuth subnitrate on the in vitro growth of major mastitis pathogens was already described by others [54]. Therefore, our study data suggest that a quarter is more likely to be colonized with S. chromogenes IM during the entire dry period if a dose of 10 000 000 CFU is used in a quarter that is not sealed.…”
Section: Discussionsupporting
confidence: 72%
“…Bonsaglia et al ( 25 ) also found lower Chao1 and Shannon indices at DIM 7 with teat sealant compared to the combination of antibiotic plus teat sealant, though not significant. Bismuth subnitrate products not only act as a physical barrier, but also show inhibitory effect on bacterial growth ( 16 ): this can partially explain the efficacy of bismuth-based formulations in the prevention of intramammary infections over the dry period. Other products have been tested as teat sealants for their physical-barrier action, like wax plugs or intramammary polystyrene devices, but were unsuccessful in the long-term protection of cows against IMI and mastitis ( 52 – 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Internal teat sealants (ITS) are a class of non-antimicrobial products that has proven to be just as efficacious as dry-cow therapy (DCT) in the prevention of IMI during the dry period. ITS may provide just a physical barrier or also inhibit bacterial growth ( 16 ). The use of an ITS in a SDCT program ensures that all healthy quarters have some form of protection against dry-period IMI.…”
Section: Introductionmentioning
confidence: 99%
“…Though ITS is generally considered to be a preventative tool rather than a treatment for IMI, the substantial proportion of quarters that cured their IMI after administration warrants such consideration. Bismuth subnitrate was recently reported to inhibit the growth of some mastitis-causing pathogens in vitro (Notcovich et al, 2020). This curing effect may be due to the inhibitory effects of ITS on the growth of microorganisms (Notcovich et al, 2020), but also by physical irritation of the epithelium in the teat cistern.…”
Section: Efficacy Of Itsmentioning
confidence: 99%
“…Bismuth subnitrate was recently reported to inhibit the growth of some mastitis-causing pathogens in vitro (Notcovich et al, 2020). This curing effect may be due to the inhibitory effects of ITS on the growth of microorganisms (Notcovich et al, 2020), but also by physical irritation of the epithelium in the teat cistern. As shown in Figure 5, the bismuth subnitrate component of Lockout has a monoclinic crystalline structure similar to that described for Orbeseal (Zoetis) by Kimbrell et al (2017).…”
Section: Efficacy Of Itsmentioning
confidence: 99%